The Impact of Puzzle Games on Attention and Fine Motor Abilities Upon Cases of Autism Spectrum Disorder: A Case Report - Zahra Almadani; Alifia Fitria Ningsih; Ika Purwaningsih; Angger Perdana Wibowo; Arif Pristianto; Intan Herlinawati (Physical Therapy Journal of Indonesia, 2022)
Background: Autism Spectrum Disorder (ASD) is brought on by the neurobiology process. This disorder ultimately results in the inability to communicate with others, a lack of interest, and repetitive behavior. One of the things that are most often encountered in children with ASD is reduced eye contact. Which, of course, will impact the severity of social deficits in the future. Patients with this behavior condition also experience motor impairments, particularly in fine motor abilities and eye contact difficulties. Naturally, there is a relationship between eye contact and fine motor abilities, where the intensity of the person's attention will undoubtedly predict fine motor abilities. Both abilities can be improved by solving puzzles. Playing this game might enhance focus, attentiveness, and fine motor abilities. This study aims to understand how puzzle games affect the attention and fine motor abilities of children with ASD. Case Description: The patient was five years and six months old with a genetic background and was diagnosed with ASD. This study was conducted at the Intan Child Physiotherapy Clinic (IFA), Boyolali. The length of time the child can maintain eye contact with objects during an attention evaluation will be used by the therapist to gauge the fine motor skills and assess how well the youngster grasps and pinches objects. Observational data-gathering approaches are employed throughout therapy. Results: The patient's capacity for eye contact attention was worth 1 second, whereas the capacity for attention to objects was 30 seconds. The number for grabbing was three (plenty), whereas the value for pinching was one and a half (very little). Conclusion: There was no significant improvement in both attentional and fine motor skills.